Simultaneous osteosarcoma in two limbs of a Maltese dog - Gorza, Leonardo L.; Brasileiro, Paula P.; Flecher, Mayra C.; Souza, Tayse D.; Horta, Rodrigo S. (Brazilian Journal of Veterinary Pathology, 2019)
Osteosarcoma (OSA) is rarely diagnosed in small breed dogs and it is usually restricted to a single bone, despite its aggressive biological behavior. This paper aims to report a rare case of OSA in an eight-year-old female spayed Maltese dog with simultaneous presentation in thoracic and pelvic limbs, associated with lung and kidney micrometastasis. Physical exam revealed an increase volume in the distal region of the left femur and in the proximal region of the left humerus with intense pain sensibility at palpation. Pelvic limb´s radiographs revealed an extensive area of bone lysis in the distal femur, lamellated periosteal reaction and formation of the Codman triangle, while in the thoracic limb, it was evident a cortical fracture of the proximal humerus and mixed periosteal reaction, suggestive of neoplastic or infectious disease. Cytological analysis showed the presence of a large number of malignant star-shaped cells, with prominent anisocytosis and anisokaryosis, moderate to prominent cellular and nuclear pleomorphism, rare mitotic figures, besides abundant extracellular matrix compatible with osteoid, suggestive of osteosarcoma. Histopathological findings were compatible with OSA. The dog died of a cardiorespiratory arrest and necropsy revealed a grade II osteoblastic osteosarcoma in the humerus and femur, along with renal metastasis and neoplastic emboli in the kidney and lungs.